Conductive Hybrid Cu‐HHTP‐TCNQ Metal–Organic Frameworks for Chemiresistive Sensing. (3rd December 2021) - Lüder, Lars; Gubicza, Agnes; Stiefel, Michael; Overbeck, Jan; Beretta, Davide; Sadeghpour, Amin; Neels, Antonia; Nirmalraj, Peter N.; Rossi, René M.; Toncelli, Claudio; Calame, Michel
Abstract: Electrically conductive metal–organic frameworks (MOFs) and MOF‐like coordination polymers are an emerging class of materials that combine good electrical charge transport with unique properties such as nanoporosity. The combination of different metal nodes and organic linkers allows tailoring MOFs to specific properties and applications in electronics, like selective chemiresistive sensing. The intrinsic crystallinity of MOFs, which usually promotes efficient charge transport, makes them also difficult to integrate into flexible systems, as crystalline MOFs are often brittle. The present study reports on a fast and reliable interfacial synthesis of conductive MOF films composed of two different organic ligands, 2, 3, 6, 7, 10, 11‐hexahydroxytriphenylene (HHTP) and 7, 7, 8, 8‐tetracyanoquinodimethane (TCNQ), lacking long‐range periodic order while preserving good electrical conductivity of 0.033 S cm −1 at room temperature and chemiresistive response toward ambient changes. The hybrid nature of the discontinuous film is investigated multiparametrically by electron and atomic force microscopy as well as by Raman spectroscopy. This study demonstrates that including different types of MOFs is a good compromise between structural order and conductivity, thus making hybrid framework architectures to a promising active material for chemiresistive sensors without the need for high crystallinity. Abstract : A fast interfacial synthesis method produces novel hybrid metal–organic framework (MOF) films consisting of two different organic ligands with good electrical conductivity despite a lack of long‐range periodic order. Various characterization techniques generate a deeper understanding of those MOF films and demonstrate a potentially good applicability for future chemiresistive sensing devices.